2017
DOI: 10.1002/jum.14428
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Bowel Findings in Male Siblings With a Confirmed FOXP3 Mutation

Abstract: There are multiple etiologies for fetal dilated bowel loops on ultrasonography (US), and we present a unique case of male siblings with a forkhead box P3 (FOXP3) mutation. Both children presented with fetal bowel anomalies on prenatal US. Family histories of cystic fibrosis and immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome were reported. Amniocentesis in both pregnancies identified a normal male karyotype and the familial mutation associated with IPEX syndrome. IPEX syndrome i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…CD4 + CD25 + Treg cells are generated in the thymus and have been reported to mitigate autoimmune myocarditis [19]. The dysfunction of CD4 + CD25 + Treg cells may lead to RHD occurrence and FoxP3 regulates Treg cell development and function [20, 21]. CD4 + IL-17 T cells have been reported to be associated with bacterial infection and inflammatory responses [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…CD4 + CD25 + Treg cells are generated in the thymus and have been reported to mitigate autoimmune myocarditis [19]. The dysfunction of CD4 + CD25 + Treg cells may lead to RHD occurrence and FoxP3 regulates Treg cell development and function [20, 21]. CD4 + IL-17 T cells have been reported to be associated with bacterial infection and inflammatory responses [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al (17) described a 37-week small-for-gestational age neonate with a new FOXP3 mutation (c.1227_1235delTGAGCTGGA), who developed IDDM on the 2nd day of life, and refractory diarrhea on day 13th, and did not survive. The two siblings described by Griswold et al (16), reported because of their ultrasonographic bowel features, presented IPEX manifestations in the 1st days of life and had a confirmed FOXP3 mutation (c.1150A > G). The family described by Levy-Lahad and Wildin (5) had three siblings with severe intrauterine growth restriction, neonatal IDDM, and enteropathy, none of them surviving.…”
Section: Echogenic Bowelmentioning
confidence: 94%
“…Prenatal ultrasonography exploration revealed bowel anomalies in all individuals, except one, whose analyses were described: hyperechoic bowel, prominent fluid-filled loops of bowel, and echogenic debris in the stomach being the most frequent findings (6,7,11,12). Griswold et al (16) observed dilated loops of bowel in two IPEX fetuses from the same family, who had manifestations in the neonatal period. In cases with severe dermatitis, hyperechoic skin with projections was described (7,12).…”
Section: Clinical Imaging and Histopathologic Features Of Intrautermentioning
confidence: 97%
See 2 more Smart Citations